Intracoronary demonstration of adenosine-induced coronary collateral steal. Issue 1 (January 1997) - Seiler, C.; Kaufmann, U.; Meier, B.
Abstract : A steal phenomenon was detected by intravascular Doppler guidewire in a patient with a well collateralised coronary vascular area supplied by a reopened left circumflex coronary artery. This phenomenon accounted for the fall in blood flow velocity reserve during hyperaemic conditions to 50% of the baseline value. The collaterals must have been the cause of the steal phenomenon because complete revascularisation of the lesion barely reversed it.